Social Movements in 1980s Sweden Contention in the Welfare State - Hill, Helena; Pinto, Andrés Brink (Palgrave Studies in the History of Social Movements,, 2023)
This open access book discusses the emergence and development, and in some cases also the disappearance, of social movements and activism in Sweden during the 1980s. Its aim is to nuance and problematize the image of the 1980s as unilaterally dominated by right-wing politics and neoliberalism, as well as the idea of a conflict-free Scandinavian model. The 1980s have often been described as a period when the influence of radical-left movements during the 1970s diminished. Instead, this book argues that the 1980s was a decade in which new radical social movements emerged in opposition to the prevalent political order, including the nuclear disarmament movement, the women's movement, anti-fascist movements, and the punk and environmental movements. The authors also demonstrate how issues such as squatting, nuclear resistance, rent strikes and the environment, included a variety of contentious collective action. Sweden, therefore, presents an interesting example of how resistance and conflict in a strong welfare state have been influenced by contentious social movements. Placing Sweden within the wider context of Scandinavia and Europe, this edited collection makes an important contribution to the history of social movements. Helena Hill is Associate Professor of the History of Ideas and Lecturer in Gender Studies at Södertörn University in Sweden. Helena's main research areas are social and political movements, gender and sexuality in a historical perspective and gender equality. Andrés Brink Pinto is Associate Professor of History and Researcher in Gender Studies at Lund University in Sweden. Andrés' main research areas are radical social movements, urban history and the history of sexuality.